Marine actinomycetes: a hidden treasure trove for antibacterial discovery - Chengqian Pan; Syed Shams ul Hassan; Muhammad Ishaq; Shikai Yan; Huizi Jin (Frontiers in Marine Science)
Oceans boast a substantial microbial diversity, which is widely prevalent in seawater, marine sediments, and marine organisms. In contrast to terrestrial resources explored in traditional natural product research, the habitats of marine microorganisms are distinctly unique. Actinomycetes serve as a vital source of secondary metabolites, including antibiotics and other potent natural products like streptomycin and tetracycline. They have played a pivotal role in clinical treatments for significant diseases such as pathogenic bacterial infections. Nevertheless, the extensive use of antibiotics has led to a sharp increase in the variety and number of drug-resistant bacteria, notably multidrug-resistant (MDR) and extensively drug-resistant (XDR) bacteria, in clinical settings, posing a grave threat to human survival. Consequently, there is an immediate need to discover structurally novel antibacterial natural products and develop new antibiotics. This mini review summarizes a total of 45 novel antibacterial natural products derived from marine actinomycetes, published in 2024. These products, including polyketides, alkaloids, macrolactams, and peptides, are highlighted in terms of their structures and biological activities. The objective of this article is to provide valuable insights for the research and development of novel antibiotics.